The morphotropic phase boundary in the (1 - x)PbZrO 3-x [0.3Bi(Zn 1/2Ti 1/2)O 3-0.7PbTiO 3] perovskite solid solution - Sareein T. (2014)
Ceramics in the (1 - x)PbZrO 3-x[0.3Bi(Zn 1/2 Ti 1/2)O 3-0.7PbTiO 3] solid solution system with 0.48< x ≤ 0.56 were investigated. A morphotropic phase boundary separating rhombohedral and tetragonal perovskite phases was identified at x = 0.52. This composition displays the maximum remanent polarization P r of 40.7 μC/cm 2 and the best piezoelectric coefficient d 33 of 311 pC/N in the pseudobinary system. However, the Curie temperature T c for this MPB composition is 291 °C, much lower than initially expected. © Springer Science+Business Media, LLC 2011.